Modeling factors influencing the intention to adopt Internet-Assisted Language Learning (IALL) by Yemeni English major students - Abdulwahab Aldaba, Abdulmajid Mohammed (Kulliyyah of Education, International Islamic University Malaysia, 2019)
Despite the benefits that Internet assisted language learning (IALL) has to offer, coupled with the ubiquity of internet technology, the adoption of IALL tools in language learning in Arab countries in general, and in Yemen in particular, is not as widespread as expected. Hence, the focus of this research is to explain English major students' intention to adopt IALL through cognitive behavioral lenses. It also sought to identify the current adoption of IALL tools by English major students. The conceptual framework of the study is represented by extended Technology Acceptance Model (TAM) with the inclusion of objective knowledge, subjective knowledge and IALL interactivity as exogenous variables. The study first seeks to examine how well core TAM constructs explain Yemeni English major students' intention towards adoption of IALL tools. Also, of particular interest to this study is the role that objective and subjective knowledge play in influencing intention towards adoption of IALL through attitude and IALL interactivity through perceived usefulness. This study also identifies the role of students' gender and academic achievement as moderating variables that influence English major students' intention to adopt IALL tools. The study adopted a quantitative approach using a survey method. The measures for research constructs were adapted from among the existing reliable instruments in the literature. However, the measure of objective knowledge as well as the checklist to profile IALL tools current adoption were specifically developed for the purpose of this study. The population under study is identified as all registered English major students in Sanaa University which is the main and biggest public university in Yemen. Therefore, the total list of the registered English major students was taken as the sampling frame. From this sampling frame, a sample of 1000 respondents was drawn on the basis of simple random sampling. The full-fledged SEM modeling was adopted as the analytical procedure. The results of the study regarding profile of the current adoption of IALL tools by English major students, shown low adoption of these tools (overall mean = 2.14). The confirmatory factor analysis (CFA) provided evidence for the convergent and discriminant validity of the study constructs. The hypothesized structural model explained indirect explanatory strength for IALL interactivity, subjective knowledge and objective knowledge in English students' intention to adopt IALL using perceived usefulness and attitudes as mediators fits the data well. Furthermore, the results of the study showed that both English major students' gender and academic achievement have significant moderating impact on their intention to adopt IALL. The model explained 71% of variance in Yemeni English major students' intention to adopt IALL tools. It could be concluded that, the extended TAM framework explains Yemeni English major students' intention to adopt IALL well.